Quantitative and qualitative analysis of antibiotic use among neonatal patients in teaching hospitals in Indonesia - Yulistiani; Kristanti Lestari; Febriansyah Nur Utomo; Mahendra Tri Arif Sampurna (Pensoft Publishers, 2024)
Patients in the neonatal intensive care unit (NICU) are at a heightened risk of bacterial infection. The administration of antibiotics in the NICU varies widely, and inappropriate use can cause resistance, underscoring the need to monitor rationale use through an antimicrobial stewardship program. Therefore, this study aimed to evaluate the quantity and quality of antibiotic prescriptions for neonates in the NICU at Airlangga University Hospital. A retrospective observational study was conducted on patients admitted to the NICU from January 1, 2021, to December 31, 2022. The quantity of antibiotics was determined using the defined daily dose (DDD) method, and the quality of prescriptions was evaluated using the Gyssens algorithm. The results showed that based on the quantitative analysis using the DDD 100 patient-days method, the most common antibiotic used was ampicillin-sulbactam. Meanwhile, the qualitative study using the Gyssens method showed that 91% of antibiotic use was in category 0 (rational).